1996
DOI: 10.1007/s0021663560311
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Chromatographic and spectroscopic techniques to study the oxidation kinetics of selenomethionine

Abstract: Ion-exchange LC and spectroscopic supporting techniques have been successfully used to study the kinetics and mechanism of oxidation reactions of selenomethionine (SeMet). Oxidation of selenomethionine with both cyanogen bromide (CNBr) and hydrogen peroxide (H(2)O(2)) proceeds through a stable intermediate which undergoes cyclization and C-Se bond cleavage to form 2-amino-4-butyrolactone. This stable intermediate was identified by IR spectroscopy as methionine dihydroxy selenide. The CH(3)-Se moiety of SeMet f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
3
9
0
Order By: Relevance
“…The formation of the hydrate under such acid conditions has been reported elsewhere. 30,31 The mass spectrum of oxidized selenomethionine was confirmed as reported by Bird to indicate the presence of hydrated selenomethionine selenoxide with a selenium ion cluster (Se-80 molecular ion at m/z 232). 32 Larsen et al have described an ion exchange HPLC-ICP-MS study in which selenomethionine selenoxide was observed and confirmed.…”
Section: Oxidation Of Selenoamino Acidssupporting
confidence: 55%
“…The formation of the hydrate under such acid conditions has been reported elsewhere. 30,31 The mass spectrum of oxidized selenomethionine was confirmed as reported by Bird to indicate the presence of hydrated selenomethionine selenoxide with a selenium ion cluster (Se-80 molecular ion at m/z 232). 32 Larsen et al have described an ion exchange HPLC-ICP-MS study in which selenomethionine selenoxide was observed and confirmed.…”
Section: Oxidation Of Selenoamino Acidssupporting
confidence: 55%
“…Se(IV) 1,000 mg/l stock solution was obtained from Merck. Selenomethionine-Se-oxide (SeOMet) was prepared as presented previously (Zainal et al 1996). For chromatographic purposes, NH 4 H 2 PO 4 , NH 4 OH, H 3 PO 4 , concentrated HCOOH, HCl, NaOH and pyridine were obtained from Reanal (Budapest, Hungary).…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism and products of the spontaneous oxidation of SeMet are unknown, and the literature of Se chemistry is not terribly helpful in identifying likely candidates. Spontaneous breakdown of SeMet in aqueous solution has been reported [5], although temperatures above ambient or storage in sunlight were required for breakdown on a timescale of one year [6]. Neither of these studies addressed the question of SeMet breakdown within a protein.…”
Section: Chemical Effects Of Semet Substitutionmentioning
confidence: 99%